Perbedaan Pelatihan Lari Aerobik 2,4 Km Dengan Takaran yang Sama di Dalam dan di Luar Lapangan Meningkatkan Kebugaran Jasmani Mahasiswa Fik Unima - Fentje Welliam Langitan (Peneliti.net, 2023)
Physical fitness provides great benefits for increasing work productivity if done properly and correctly. Physical fitness will make a significant contribution to the ability to work and physical activity. The aerobic running program is a program that aims to improve physical fitness. However, the right way or method and environment help improve the body effectively and efficiently. This study used a quasi-experimental method with a randomized pretest-posttest group design. The place for conducting the research is at the Manado State University Stadium/field, with a research implementation time of 6 weeks, which applies from February to August 2022. The data analysis technique used was the t-test which was previously preceded by a data normality test with Kolmogorov Smirnov and Data homogeneity with the Levene test. Therefore, aerobic training of 2.4 kilometers inside the stadium/field with a frequency of training three times a week for 6 weeks is better at improving physical fitness than training running 2.4 kilometers outside the stadium/field with a frequency of training three times a week for 6 weeks.